Indispensable Role of HIF-1α Signaling in Post-implantation Survival and Angio-/Vasculogenic Properties of SHED - Han, Yuanyuan; Chen, Qixin; Zhang, Lili; Dissanayaka, Waruna Lakmal (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Post-implantation survival and timely vascularization of stem-cell based constructs are critical factors in achieving successful outcomes in tissue regeneration approaches. Hypoxia inducible factor-1α (HIF-1α) is known to mediate adaptive functions to ischemic stress in many different cell types. The current study aimed to explore the role of HIF-1α in post-implantation survival and angio-/vasculogenesis of stem cells from human exfoliated deciduous teeth (SHED). Methods: HIF-1α in SHED was suppressed using siRNA or chemical inhibitor (YC-1) and used in Matrigel plug assay conducted on severe combined immunodeficient (SCID) mice. The plugs were retrieved on day 3 or 7 post-injection and analyzed for hypoxia status, ki67 expression, DNA fragmentation (TUNEL), cellularity, and vascularization by histology and immunohistochemistry (IHC) for CD31, HIF-1α, PDK1, HK2, and Glut1. Cell viability of HIF-1α silenced SHED under different stress conditions (hypoxia, H2O2, and low glucose) in vitro was measured by CCK-8 assay. CM-H2DCFDA and MitoSOX Red were used to detect cellular and mitochondrial reactive oxygen species (ROS) levels, respectively. PDK1, HK2, and Glut1 expression were measured by western blotting and immunofluorescence. Secretory protein levels of vascular endothelial growth factor (VEGF) and the respective paracrine effects on endothelial cell proliferation and migration were detected by ELISA, CCK-8 assay, and trans-well assay, respectively. Results: Histological analysis of Matrigel plugs showed significantly reduced cell survival in HIF-1α silenced or chemically inhibited SHED groups, which could be attributed to diminished metabolic adaptations as shown by decreased PDK1, HK2, and Glut1 expression. HIF-1α inhibition in SHED also resulted in significantly low blood vessel formation as observed by a low number of perfused and non-perfused vessels of human or mouse CD31 origin. The viability of HIF-1α silenced SHED was significantly affected under hypoxia, H2O2, and low-glucose conditions in vitro, which was reflected in increased cytoplasmic and mitochondrial ROS levels. Significantly reduced levels of VEGF in HIF-1α silenced SHED resulted in decreased paracrine angiogenic effects as shown by low proliferation and migration of endothelial cells. Conclusion: HIF-1α plays an indispensable role in post-implantation survival and angio-/vasculogenic properties of SHED by maintaining ROS homeostasis, inducing metabolic adaptations, and VEGF secretion.